PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SD NEGERI I PEUSANGAN BIREUEN ACEH - Rahman, Aisyah A. (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
This research was aimed to identify the differences and influences of pictorial media to the achievement of tenth grade students in Public Elementary School 1 Peusangan Bireuen Aceh, in the material of natural appearance and social condition in Neigborhoud Countries. The method used in this research was quasi experiment, i.e. a method to identify the influence of other variables to a specific variable. Two variables were analyzed in this research: (1) pictorial media as independent variable, and (2) students’ achievement as dependent variable. Analysis resulted in a significant influence of pictorial media to students’ achievement in geographic. It was showed by the value of t = 2.811 and two-tailed significance of 0,006, which resulted in p 0,05. Based on this result, it was decided that Ho cannot be accepted and H1 is accepted. Thus, it was concluded that there is a significant difference between students learning using pictorial media and students learning without pictorial media (focused on text book only).Key words: Pictorial media, learning achievement